Decolonizing Academic Funding: An Evaluation of an Indigenous Collaborative Funding Initiative - Fournier, Cathy; Stewart, Suzanne; Adams, Joshua; Shirt, Clay; Mahabir, Esha; Pinkoski, Cohen (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2024)
In 2020 an innovative Indigenous community-led internal funding initiative was undertaken at a major university in Canada, followed in 2022 by a qualitative study of its inaugural round. This funding initiative is unique in that each research project was first identified by an Indigenous community/organization through a Canada-wide outreach process. The outreach process involved reaching out to over 700 Indigenous communities and organizations, via email or telephone, to ask if they would be interested in participating in a funded research project they identified as important and beneficial. The role of the university academic research partners was that of mentor rather than principal investigator for each project. Nine community-led research projects were funded and are currently underway. In this paper the authors outline the process of developing the initiative, its components, and findings from the study. Successes and challenges of the funding model are identified followed by a discussion of emergent themes. One of the key themes that emerged is that although there are aspects of this initiative that met its intended goals, it highlights a barrier in meeting one of the objectives, contributing to Indigenous research governance and self-determination.